Distribusi Pupuk Non Subsidi Pada PT Sang Hyang Seri (PERSERO) Bengkulu Marketing Branch Office - Nurbaiti, Meri; Yuristia, Rahmi; Badrudin, Redy (LPPM Universitas Malikussaleh - Indonesia, 2023)
Agriculture as a vital role in the Indonesian economy in meeting all the basic needs of the community requires supporting factors in the production process. Fertilizers have an important role in increasing agricultural productivity, so it is necessary to distribute fertilizers evenly throughout the region. PT Sang Hyang Seri (Persero) Bengkulu marketing branch office is a subsidiary of a state-owned company that is a distributor of non-subsidized fertilizers in the Bengkulu region. This research was conducted using data tabulation and table matrix methods with data obtained from observations and interviews. This research shows that PT Sang Hyang Seri (Persero) Bengkulu marketing branch office distributes three types of non-subsidized fertilizers in the form of SP-18 Bintang Kuda Laut, KCl Ex Belarus, and NPK Jatiwangi with two marketing alternatives, which are directly to farmers and through kiosk intermediaries. In addition, in its distribution there are five obstacles experienced, namely, 1) price competition; 2) uncertain availability of non-subsidized fertilizer stocks; 3) farmers' purchasing decisions; 4) still lack of maximum promotion; and 5) still lack of human resources.